The Crash of the millennium surviving the coming inflationary depression - Batra, Ravi (New York Harmony Books)
The premise of this book is as simple and as powerful as the law of supply and demand. In the United States, as in many other countries we've been producing more and more goods, but wages have not kept pace. The disparity has been papered over by credit c
Keywords: Investment-United States; Finance, Personal-United States; Business cycles-United States; Economic forecasting-United States